IMPLEMENTATION OF THE PRISONER DEVELOPMENT PROGRAM BULUKUMBA CLASS IIA CORRECTIONAL INSTITUTION - Putri, Tasya Wardana; Aslinda, Andi; Halim, Didin (Jurnal Aktor, 2025)
This study aims to find out and explain the Implementation of Prisoner Development in Class II A Bulukumba Correctional Institution. To achieve the goal, the researcher uses data collection techniques through observation, interviews and documentation. The data obtained from the results of the research were processed using qualitative descriptive information on the Implementation of Prisoner Development in Class II A Bulukumba Correctional Institution. The results of the researcher show that the Implementation of the Development of Inmates in Class II A Bulukumba Correctional Institution has gone well in the indicators of Interests Influenced by the Program, Benefits Produced, Desired Changes that still need to be improved, Decision Making, Program Implementers, Available and quality resources. But on the indicator of available and quality Resources still needs to be improved